La interpretación de enunciados condicionales como bicondicionales y su problemática en la tarea de selección (2014)
On several occasions, conditional statements are perfected, that is, are understood as biconditional statements. This causes problems for texts interpretation in general and for the correct understanding of the instructions of the selection task in particular. Usually, the results of this task are unexpected and, due to this, theories have been raised in order to try to explain them from hypotheses about certain mental mechanisms or special types of reasoning in human beings. In this paper, I try to demonstrate, through a critical review of a particular experiment in the literature, that it is not necessary to assume such hypotheses and that it is possible to explain what happens in such experiment simply assuming that participants perfect some conditional rules proposed in it.